Studi Observasional Kesalahan Pengobatan di Depo Farmasi Rawat Jalan RSUP Dr. Hasan Sadikin Bandung - Viki Hestiarini; Lia Amalia; Eni Margayani (Fakultas Farmasi Universitas Pancasila, 2017)
Medication error can occur at all stages, starting from prescribing, dispensing and administration of drugs. This study aims to assess the medication errors that occur in the pharmaceutical care process and analyze the cause of failure using the root cause analysis method, to improvement action and decrease the incidence of medication errors. The data were completeness prescription, frequency of dispensing error and completeness of drug information. The number of sample was 1100 prescriptions Prescribing errors were found the potential injury 15.69±11.51% and near missed error 0.5±0.55%. At dispensing stage, occur 427 incidences (9.71%), consist of two incidences (0.04%) for validation assessment regulations, 224 incidences (5.09%) of data entry, 113 incidences (2.57%) of retrieval of drugs, 19 incidences (0.43%) of fi ll in drugs, 69 incidences (1.57%) of fi nal check. At dispensing stage, near missed 330 incidences (7.51%) of near missed and 97 incidences (2.21%) of potential injury. Failure mode and effect analysis calculate of risk priority number, the drug retrieval (RPN 210) and data entry (RPN 126) were analyzed root cause of the analysis for man, material, method, facility and environment.